2013
DOI: 10.1891/2156-5287.3.2.76
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Support During Childbirth by Maternity Care Assistants: An Exploration of Opinions in the Netherlands

Abstract: BACKGROUND:The Netherlands maintain a high rate of home births relative to other well-resourced countries. Maternity care assistants (MCAs) play an important role, as part of the maternity care team, assisting the midwife during birth and providing postpartum care to women and babies in their homes. A Cochrane review recently described the advantages of continuous support during childbirth. We were interested in the opinions of MCAs about them having an expanded role to include continuous emotional support dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Women indicated that they preferred the midwife to remain present for a longer period of time. Furthermore, some women suggested the midwife could improve her profession by not attending to more births at the same time, being on time at the birth, and providing more care directly after the birth (on call shifts of Dutch midwives are described in detail by Baas et al ).
Take more time for the check‐ups, which are now so rushed that I only dare to ask the most necessary. Questions that have a lower priority, I search on the Internet.
…”
Section: Coordination Of Carementioning
confidence: 86%
“…Women indicated that they preferred the midwife to remain present for a longer period of time. Furthermore, some women suggested the midwife could improve her profession by not attending to more births at the same time, being on time at the birth, and providing more care directly after the birth (on call shifts of Dutch midwives are described in detail by Baas et al ).
Take more time for the check‐ups, which are now so rushed that I only dare to ask the most necessary. Questions that have a lower priority, I search on the Internet.
…”
Section: Coordination Of Carementioning
confidence: 86%